2015
DOI: 10.1109/tdei.2015.005062
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of electric conduction in mineral oil by time domain and frequency domain measurement

Abstract: Polarization and depolarization current measurement is a non-destructive testing method to study the dielectric properties of insulating materials. Two types of mineral oils with different aging times have been studied using both time domain and frequency domain methods separately. In this paper, a novel approach to understanding the correlation between the electric conduction in time domain and frequency domain has been proposed. When the charge carriers drift to the electrodes, they may be blocked and accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The mobility of charge carriers in pure liquid hydrocarbons, obtained in [35], remains constant within a wide range of electric field magnitudes. However, in [36] it was suggested that in mineral oils the charge carriers with both, lower and higher mobilities can be present. In the present work, the mobility of charge carriers was obtained using different electric field magnitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The mobility of charge carriers in pure liquid hydrocarbons, obtained in [35], remains constant within a wide range of electric field magnitudes. However, in [36] it was suggested that in mineral oils the charge carriers with both, lower and higher mobilities can be present. In the present work, the mobility of charge carriers was obtained using different electric field magnitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou and co-workers suggested to the characterize charge carriers in mineral insulating oil by using the polarization and depolarization currents, and simulate the frequency response by the calculated insulating oil conductivity [58,59].…”
Section: Electrical Conductivity Of Mineral Insulating Oilmentioning
confidence: 99%
“…Condition monitoring of transformers helps determine the maintenance and replacement decisions of transformers [1]. The insulating oil in transformers plays the roles of coolant and insulation [2]. DC resistivity of the oil is one of key parameters to assess the transformer insulation condition, based on the fact that the DC resistivity is sensitive to the oil degradation [3].…”
Section: Introductionmentioning
confidence: 99%